(untitled) (Revista Brasileira Multidisciplinar, 2025)
The genus Listeria is a group of bacterial species that are highly pathogenic in humans. It has been identified in a range of foods, particularly animal products, acting as a conduit for pathogens to humans and a reservoir for antibiotic-resistant microorganisms. The objective of the study was to investigate the prevalence and antimicrobial resistance of Listeria spp. in fish sold in Cuiabá, Mato Grosso, Brazil. A total of 72 samples of two species of freshwater fish were obtained and separated into 12 combinations, resulting from the interaction of three factors: species (leather/scale), marketing methods (fresh/frozen), and establishments (market/fish market). The presence of Listeria spp. was confirmed in 44 samples, with the highest occurrence of Listeria innocua. The examination of the data revealed that the species was the sole factor associated with the presence of Listeria spp. It was observed that leather fish exhibited a higher susceptibility to contamination. The isolates demonstrated high resistance to oxacillin (88.72%) and greater sensitivity to chloramphenicol (100%). Accordingly, the identification of this microbial agent within the samples under investigation underscores the imperative for monitoring its prevalence. In this context, chloramphenicol represents the preferred antibiotic for the eradication of Listeria spp.